Experimental identification and prioritization of design and process parameters on hole fill in mini wave soldering - Seidel, Reinhardt; Ahrens, Thomas; Friedrich, Jürgen; Reinhardt, Andreas; Franke, Jörg (Microelectronics Reliability, 2022)
Mini wave soldering is a common method for soldering through-hole components on printed circuit boards (PCB). With PCB design becoming increasingly complex and copper layer thickness rising, the vertical hole fill of through-hole solder joints becomes a serious problem during manufacturing. At the same time, the process window is limited by limited material heat resistance of the PCB and the through-hole components. Especially critical is latent damage inside the PCB and the through-hole component which must not exceed its specific maximum core temperature because this would compromise reliability over lifetime. The choice of soldering parameters is critical to reaching sufficient vertical fill to achieve a reliable connection according to IPC-A-610. The dedicated description of the interaction between PCB design and vertical fill has the potential to considerably improve the understanding of the basics of design for manufacturing (DfM). In this paper, the essential process parameters of the selective wave soldering process are examined by design of experiment (DoE) with respect to hole fill, which determines mechanical and thermal reliability as well as current carrying capacity. The results show the individual effects of the copper layer design parameters including layer count, layer thickness, hole copper plating attachment and solder alloy on vertical hole fill, in combination with the solder process parameters. The copper layer design parameters, solder bath temperature and preheating temperatures show the strongest effects. The soldering time has the lowest impact within the tested process parameters. For a given solder joint with its defined heat capacity, the benefit of solder time diminishes the longer the contact time is. Component surfaces and connector pin material and machine parameters like pump power as well as environmental conditions show little to no impact within a reasonable operation window.<br
Keywords: Selective wave soldering; THT component; Design of experiments; Hole fill